The Lean Design of Manufacturing Process - Dana Strachotová (Contemporary Economics)
This article is intended to using of Six Sigma methodology. A break trough strategy to significantly improve customer satisfaction and shareholder value by reducing variability in every aspects of business. It enhances the ability to delivery customer satisfaction and cost improvement results faster – within months from the start, and sustains the rate of improvement on-going. One of the most powerful ways to improve business performance is combining business process management (BPM) strategies with Six Sigma strategies. BPM strategies emphasize process improvements and automation to drive performance, while Six Sigma uses statistical analysis to drive quality improvements. The two strategies are not mutually exclusive, however, and some savvy companies have discovered that combining BPM and Six Sigma can create dramatic results. Six Sigma methodology teaches and deploys hard skills and business practices emphasizing.